2023
DOI: 10.1002/job.2710
|View full text |Cite
|
Sign up to set email alerts
|

Energy, attentional resources and work–family conflict over the meso‐term: Resource loss spirals revisited

Abstract: Resource‐based theories specify personal resources as a central cause and outcome of work–family conflict wherein low personal resource levels beget further resource losses, in part through increased work–family conflict. Yet, adaptation and trait theories suggest chronic factors drive stability in personal resources and work–family conflict, potentially making resource loss spirals unlikely for most workers. Despite being fundamental tenets of resource‐based theories of work–family conflict, the causal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 102 publications
(168 reference statements)
1
15
0
Order By: Relevance
“…Our selection of lags was based on Dormann and van de Ven (2014) temporal lag taxonomy such that we used two mid-term designs-a 1-week lag over four assessments in Study 1, and a 1-month lag over five assessments in Study 2. Two mid-term temporal lags were selected because they align well with DET, our guiding theoretical framework (Dormann & van de Ven, 2014) and are consistent with existing mistreatment measurement work as well as recent empirical treatments of temporal dynamics (Ford et al, 2023).…”
Section: Programme Of Researchmentioning
confidence: 98%
“…Our selection of lags was based on Dormann and van de Ven (2014) temporal lag taxonomy such that we used two mid-term designs-a 1-week lag over four assessments in Study 1, and a 1-month lag over five assessments in Study 2. Two mid-term temporal lags were selected because they align well with DET, our guiding theoretical framework (Dormann & van de Ven, 2014) and are consistent with existing mistreatment measurement work as well as recent empirical treatments of temporal dynamics (Ford et al, 2023).…”
Section: Programme Of Researchmentioning
confidence: 98%
“…Analyzing their three-wave data (time lags: 3 months), these authors found significant negative crosslagged paths from qualitative job insecurity to participation in formal and some types of informal learning as well as reverse negative paths from participation in formal learning to qualitative job insecurity. Ford et al (2023) relied on a general cross-lagged panel model and analyzed how energetic and attentional resources relate to work-family conflict (work-to-family conflict, family-to-work conflict) over time. Using four-wave data (time-lags: 1 month), they found that low energetic and attentional resources predicted an increase in work-to-family conflict from one month to the next, and that work-to-family conflict predicted a decrease in attentional-but not energetic-resources.…”
Section: Examples Of Studies Aiming At a Test Of Gain And Loss Cycles...mentioning
confidence: 99%
“…Second, there was heterogeneity in the time lags between measurement points. Time lags ranged from one month (Ford et al, 2023) to three years (Hakanen et al, 2011). This variety in time lags implies that it is difficult to draw firm conclusions about how much time is needed for gain and loss cycles to unfold.…”
Section: Examples Of Studies Aiming At a Test Of Gain And Loss Cycles...mentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to, for example, resource theories, theories of motivation are an underutilized perspective in the work–family literature. Moreover, given that resource theories have come under increased scrutiny by work‐family scholars (e.g., Ford et al, in press), motivational theories have particular promise for enhancing our understanding of experiences in work and family roles. Motivation theories are often organized as content, context, and process theories (Kanfer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%